The management of the Sars-CoV-2 pandemic in Italy, lessons earnt and reflections for the future - Maffeo, Manuel; Azara, Antonio; Di Rosa, Enrico; Bertinato, Luigi; Garbelli, Claudio; Castaldi, Silvana (Acta Biomedica Atenei Parmensis, 2021)
Background: Italy and especially Lombardy region was the first European Country hit by the covid 19 pandemic, without a proper preparedness plan. Italy’s health-care service is a regionally based National Health Service (NHS) that provides universal coverage, largely free of charge at the point of service. Aim of this paper is to analyse the national and especially the regional strategies put in place to face the pandemic, focusing on the impact of the overlap of the political and health competences among national and regional authority. Methods: Italian hygiene and preventive medicine society (SITI) realized a questionnaire submitted to National Institute for Health and regional stakeholder to investigate the response to the epidemic analysing the strategies and actions put in place both by the national and regional governments and the regional health authorities. Results: The national survey highlighted several critical points in the management of the covid 19 pandemic in the different regional contexts such as lack of personnel in preventive departments and preparadness. Conclusions: Lessons learnt during the pandemic should shape the future of the Italian health service. (www.actabiomedica.it)